2013
DOI: 10.1080/03235408.2013.820387
|View full text |Cite
|
Sign up to set email alerts
|

Pome and stone fruit trees as possible reservoir hosts forPhaeoacremoniumspp., the causal agents of grapevine esca disease, in Iran

Abstract: Phaeoacremonium spp. are known as the main Hyphomycetes associated with esca disease symptoms on grapevines worldwide. The role of other woody hosts in proximity of vineyards as a possible inoculum source for the causal agents of grapevine esca disease mainly remains unknown. The aim of this study was to investigate the occurrence of Phaeoacremonium spp. on pome and stone fruit with trunk diseases symptoms in northwestern parts of Iran. For this purpose, wood trees samples were collected from apple and apricot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“… South Africa (this study) Olea europaea subsp. europaea Italy ( Crous & Gams 2000 );South Africa (this study); USA ( Úrbez-Torres et al 2013 ) Parrotia persica Iran ( Kazemzadeh Chakusary et al 2017 ) Phoenix dactylifera Iran ( Mohammadi 2014 ) Prunus armeniaca Iran ( Arzanlou et al 2014 ) ; South Africa ( Damm et al 2008b ) Prunus dulcis South Africa (this study) Prunus pennsylvanica USA ( Hausner et al 1992 ) Prunus persica South Africa ( Damm et al 2008b ) Prunus salicina South Africa ( Damm et al 2008b ) Psidium guajava South Africa (this study) Punica granatum South Africa (this study) Pyrus communis Iran ( Sami et al 2014 ); South Africa ( Cloete et al 2011 ) Rosa sp. South Africa (this study) …”
Section: Appendixmentioning
confidence: 89%
“… South Africa (this study) Olea europaea subsp. europaea Italy ( Crous & Gams 2000 );South Africa (this study); USA ( Úrbez-Torres et al 2013 ) Parrotia persica Iran ( Kazemzadeh Chakusary et al 2017 ) Phoenix dactylifera Iran ( Mohammadi 2014 ) Prunus armeniaca Iran ( Arzanlou et al 2014 ) ; South Africa ( Damm et al 2008b ) Prunus dulcis South Africa (this study) Prunus pennsylvanica USA ( Hausner et al 1992 ) Prunus persica South Africa ( Damm et al 2008b ) Prunus salicina South Africa ( Damm et al 2008b ) Psidium guajava South Africa (this study) Punica granatum South Africa (this study) Pyrus communis Iran ( Sami et al 2014 ); South Africa ( Cloete et al 2011 ) Rosa sp. South Africa (this study) …”
Section: Appendixmentioning
confidence: 89%
“…While some of these fungal species have proven to be pathogenic on grapevine, the pathogenic potential of many species still remains to be tested. Recent studies have shown that other woody hosts serve as alternative or reservoir host for grapevines trunk pathogens; hence, there is growing attention on truck diseases of other woody host plant species, particularly in vicinity of vineyards (Arzanlou et al ; Gramaje et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…While some of these fungal species have proven to be pathogenic on grapevine, the pathogenic potential of many species still remains to be tested. Recent studies have shown that other woody hosts serve as alternative or reservoir host for grapevines trunk pathogens; hence, there is growing attention on truck diseases of other woody host plant species, particularly in vicinity of vineyards (Arzanlou et al 2013b;Gramaje et al 2016). A recent study on fungal truck pathogens of almond trees in Spain characterized several fungal groups including C. hispanica, as new species from Mean lesion length is based on three replicates per isolate (six isolates for Collophora hispanica).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though grapevine is the main host for Pm. aleophilum, it has been reported on fruit trees and other woody hosts (Mostert et al 2006;Cloete et al 2011;Arzanlou et al 2013b;Carlucci et al 2013).…”
Section: Introductionmentioning
confidence: 96%